2010
DOI: 10.1002/art.30087
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐α accelerates murine systemic lupus erythematosus in a T cell–dependent manner

Abstract: Objective. To investigate the mechanism by which interferon-␣ (IFN␣) accelerates systemic lupus erythematosus (SLE) in (NZB ؋ NZW)F 1 (NZB/NZW) mice.Methods. NZB/NZW mice were treated with an adenovirus expressing IFN␣. In some mice, T cells were depleted with an anti-CD4 antibody. The production of anti-double-stranded DNA (anti-dsDNA) antibodies was measured by enzyme-linked immunosorbent assay and enzyme-linked immunospot assay. Germinal centers and antibody-secreting cells (ASCs) in spleens and IgG deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
115
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 49 publications
3
115
2
1
Order By: Relevance
“…Commentary of TLR7 on B cells, T-cell-independent expansion of marginal zone B cells and high serum levels of BAFF and IL-6, autoantibody production, and clinical disease in this murine model of SLE is absolutely T-cell dependent [9]. Considering the large number of germinal centers that form, it is surprising that the multitude of plasma cells that arise 2-3 wk following IFN-a induction and persist throughout the disease are short-lived and that they fail to migrate to the BM or the inflamed kidney or survive for long periods in the spleen [8,9].…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Commentary of TLR7 on B cells, T-cell-independent expansion of marginal zone B cells and high serum levels of BAFF and IL-6, autoantibody production, and clinical disease in this murine model of SLE is absolutely T-cell dependent [9]. Considering the large number of germinal centers that form, it is surprising that the multitude of plasma cells that arise 2-3 wk following IFN-a induction and persist throughout the disease are short-lived and that they fail to migrate to the BM or the inflamed kidney or survive for long periods in the spleen [8,9].…”
mentioning
confidence: 90%
“…Considering the large number of germinal centers that form, it is surprising that the multitude of plasma cells that arise 2-3 wk following IFN-a induction and persist throughout the disease are short-lived and that they fail to migrate to the BM or the inflamed kidney or survive for long periods in the spleen [8,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that this feature might be regulated by type I IFN. IFN acts subsequent to high-affinity somatic mutations that occur within the GC reactions via the downregulation of chemotactic molecules involved in the migration of newly formed PCs to the bone marrow (72)(73)(74)(75). Our study demonstrated that B6.Sle1 lupusprone animals have an upregulated IFN signature early in life, before expansion of ASCs can be detected.…”
Section: Cd8mentioning
confidence: 64%
“…Spleen and bone marrow B cells were analyzed as previously described (21,26,27 (20). Somatic mutation rates were calculated by using a program available on the IMGT website.…”
Section: Flow Cytometry and Sortingmentioning
confidence: 99%